Pensando a Diáspora Atlântica - Silva, Lúcia Helena Oliveira (2018)
ABSTRACT The text seeks to discuss the different meanings that the term diaspora has assumed since its emergence in the early years of the twentieth century through the debates in the History of Africa, History of the Atlantic Diaspora and the contemporary senses